Характеристика окремих видів слідчого експерименту під час розслідування кримінальних правопорушень - Гусєва, В. О.; Husieva, V. O.; Vlada Husieva (Судова та слідча практика в Україні. – 2019. – Вип. 8. – С. 52-56, 2019)
У статті на підставі аналізу практики органів досудового слідства, наукової літератури розглянуті питання, що стосуються характеристики окремих видів слідчого експерименту. Визначено особливості проведення слідчого експерименту під час розслідування кримінальних правопорушень, наведено приклади практичної спрямованості.

On the basis of the analysis of practice of organs of pre-trial investigation, scientific literature, questions concerning the characteristics of certain types of investigative experiment were considered. The peculiarities of conducting an investigative experiment in the investigation of criminal offenses are determined, examples of practical orientation are given. Investigation of investigative practices showed that the investigative experiment was carried out by an investigator in 63.8% of the investigated proceedings, indicating that this investigative action serves as a reliable way of obtaining evidence, verifying a person's awareness of the circumstances of the criminal proceedings. Thus, the question arises of the need for conducting an investigative experiment, since it may manifestly refute the false testimony of the suspect or be the only way to verify the testimonies of other participants in a criminal offense, and in many cases, plays a decisive role in establishing an objective truth in a criminal proceeding. We propose the following classification of types of investigative experiment: to establish the possibility of perceiving any action or fact, phenomenon; to establish the possibility of any action; to establish the possibility of the existence of any fact, phenomenon; by setting the mechanism of the event or its individual details; by setting the time it takes to spend on one or another action. The forensic classification and peculiarities of conducting an investigative experiment can be included in a separate forensic methodology, which is constructed taking into account the conditions of the Code of Criminal Procedure of Ukraine. These provisions can be used in scientific activity, pedagogical process in the teaching of criminology and in the practice of the bodies of pre-trial investigation. The development and improvement of these recommendations is a promising direction for further research.

В статье на основании анализа практики органов досудебного следствия, научной литературы рассмотрены вопросы, касающиеся характеристики отдельных видов следственного эксперимента. Определены особенности проведения следственного эксперимента при расследовании уголовных преступлений, приведены примеры практической направленности.
Characteristics of certain types of investigative experiment in the investigation of criminal offenses
Keywords: Криміналістика. Criminalistics. Криминалистика; Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; слідчий експеримент; розслідування кримінальних правопорушень; investigation of criminal offenses; investigative experiment; следственный эксперимент; расследование уголовных правонарушений